Biotin-Avidin-Mediated Capture of Microspheres on Polymer Fibers - Ahrens, Lucas (Molecules, 2019)
Systems for efficient and selective capture of micro-scale objects and structures have application in many areas and are of particular relevance for selective isolation of mammalian cells. Systems for the latter should also not interfere with the biology of the cells. This study demonstrates the capture of microspheres through orthogonal coupling using biotin (ligand) and (strept)avidin (receptor). Fibrous poly(ethylene terephthalate) (PET) meshes were hydrolyzed under controlled alkaline conditions to obtain activated surfaces with COOH groups allowing for the functionalization of the PET with biotin of various spacer length. The system capture efficiency was optimized by varying the length of spacer presenting the biotin against streptavidin. In a proof of concept experiment, avidin-functionalized microspheres were used as surrogates for cells, and their capture under dynamic conditions including virous mixing and high-flow rate perfusion is demonstrated. Functionalization of PET meshes with biotin conjugated to longest spacer yielded the most efficient capture of microspheres. These preliminary results lay the foundation for the development of biosystems for capture of specific cells under physiologically relevant conditions, using biorthogonal avidin-biotin interactions.